Conductive triethylene glycol monomethyl ether substituted polythiophenes with high stability in the doped state. Issue 10 (13th March 2019) - Dissanayake, Dushanthi S.; Gunathilake, Samodha S.; Udamulle Gedara, Chinthaka M.; Du, Jia; Yoo, Sang Ha; Lee, Youngmin; Wang, Qing; Gomez, Enrique D.; Biewer, Michael C.; Stefan, Mihaela C.
ABSTRACT: Synthesis of two conducting polymers containing 3‐hexylthiophene and 3‐[2‐(2‐(2‐methoxyethoxy)ethoxy)ethoxy]thiophene is demonstrated. In thin‐film transistors, the high‐molecular‐weight polymer shows an average mobility of 4.2 × 10 −4 cm 2 V −1 s −1 . Most importantly, the polymers have high conductivity upon doping with iodine and also have high stability in the doped state with high conductivities measured even after 1 month. Furthermore, the doping causes transparency to thin films of the polymer and the films are resistant to common organic solvents. All these properties indicate a great potential for the iodine‐doped polymer to be used as an alternative to commercially available poly(3, 4‐ethylenedioxythiophene):poly(styrene sulfonate). © 2019 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem.2019, 57, 1079–1086 Abstract : Polymers containing bithiophene with 3‐hexyl and methoxyethoxyethoxyethoxythiophene substituents were synthesized by McCullough method. The polymers showed lower band gaps as compared to poly(3‐hexylthiophene), thermal stability up to 300 °C, and conductivities of 700 S cm −1 . Iodine doping caused transparency in thin films of the polymer, and the films were insoluble in common organic solvents. In thin‐film transistors, the polymers showed an average mobility of 4.2 × 10 −4 cm 2 V −1 s −1 .